Procoagulant constituents from Cordyceps militaris - Juanjuan Zhang; Wei Zhang; Zhenhua Yin; Changqin Li; Wenyi Kang (Food Science and Human Wellness)
Cordyceps militaris, belongs to Clavicipitaceae family, was investigated for its chemical compounds, and six compounds were isolated and purified by silica gel column chromatography, Sephadex LH-20 and recrystallization, and their structures were elucidated by spectral techniques and physicochemical properties as ergosterol (1), adenosine (2), cordycepin (3), ergosterol peroxide (4), tetracosanoic acid 2,3-dihydroxypropylester (5), mannitol (6). Procoagulant activity was screened by assaying the activated partial thromboplastin time (APTT), prothrombin time (PT), thrombin time (TT) and fibrinogen (FIB) in vitro. The results indicated that ergosterol, adenosine, cordycepin, ergosterol peroxide and mannitol showed strong procoagulant activity. Keywords: Cordyceps militaris, Chemical component, Procoagulant activity, Ergosterol